“You’re on Mute” : can the workplace impact creative performance? - Caetano, Sandra Meneses (2022)
The ongoing pandemic times have most likely permanently changed the way we work. Our homes became our office, and we were now presented with the challenge of juggling professional and personal matters within the same space. Despite the unfortunate circumstances and innumerous challenges associated, it allows for a greater understanding of how working from home practices impact one’s performance and general well-being. Can working from home actually foster creativity? As previous research suggests a strong link between spatial distance and enhanced creative performance (Jia, Hirt, & Karpen, 2009), this dissertation attempted to test if the same effect applied on an extremely relevant real-life context. As such, two different studies were conducted to compare performance on creative tasks between individuals at the office and at home and test distance as a mediator of this effect. In Study 1, participants were asked to imagine themselves either working from home or at the office while in Study 2, participants were directly tested while working from home or at the office. Although individuals at home displayed a significantly superior performance than those at the office on both studies, distance alone does not seem to be the reason why.